Astronomical Photometric Calibrations at the Huancayo observatory - Baella, Nobar (2003)
We present a first determination of the atmospheric extinction coefficients and the transformation coefficients to the standard system for astronomical photometric studiesat the Huancayo's Observatory. The measurements were made using a CCD camera